Bronx SIU. Season one - Mayhall, Mike; Baraka, Ameer; Boutte, Denise, 1982-; Davenport, Eddie; Nunes, Miguel; Lowry, Shanti, 1982-; White, Brian, 1973 April 21-; RLJ Entertainment (Silver Spring, MD : RLJ Entertainment, 2018)
Follows an elite task force that investigates New York City's most difficult cases.
Pride cometh before... -- Archangels -- Welcome to the SIU -- Can we do that? -- Enter Argon -- All that matters -- Meet Jimmy Blue -- Promises to keep.
Dolby digital stereo, wide screen 1.77:1.
Features: cast/director interviews.
Ameer Baraka, Denise Boutte, Eddie Davenport, Keeland Ellis, Jillian Ferry.
Originally broadcast on television in 2018.
TV rating: Not rated.
Keywords: Murder -- Investigation -- New York (State) -- New York -- Drama; Detectives -- New York (State) -- New York -- Drama; Police -- New York (State) -- New York -- Drama; Bronx (New York, N.Y.) -- Drama; Video recordings for the hearing impaired; Television cop shows; Detective and mystery television programs; Television series; Fiction television programs